1997
DOI: 10.1097/00005344-199709000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Pressor Relevance of the Short-Term Cardiovascular and Renin Excitatory Actions of the Selective A2A-Adenosine Receptor Agonists

Abstract: Selective A2A adenosine receptor agonists are potent vasodilators that reduce blood pressure and induce marked increments in heart rate and plasma renin activity (PRA). To examine the mechanisms and pressor relevance of these cardiac and renin responses, we measured blood pressure and heart rate by telemetry and PRA in separate sets of spontaneously hypertensive rats (SHRs), which were given i.p. 2-hexynyl-5-methylcarboxamidoadenosine (2HE-NECA, 0.01 mg/kg) and 2-[4-(2-carboxyethyl)phenethylamino]-5'-N-ethylca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
25
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 9 publications
3
25
0
Order By: Relevance
“…However, studies showed that adenosine could stimulate isolated arterial chemoreceptors (McQueen and Ribeiro, 1981) and studies using selective agonists suggested that this effect was mediated by A 2A receptors Ribeiro, 1983, 1986). In animals as well as humans, adenosine and its analogs cause sinus tachycardia and lower systemic blood pressure (Biaggioni et al, 1987;Lappe et al, 1992;Bonizzoni et al, 1995;Alberti et al, 1997;Koos and Chau, 1998;Barrett et al, 2005;Hendel et al, 2005;Schindler et al, 2005). The sinus tachycardia has been attributed to the baroreceptor reflex caused by the decrease in arterial pressure (Webb et al, 1990(Webb et al, , 1991Nekooeian and Tabrizchi, 1996;Alberti et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, studies showed that adenosine could stimulate isolated arterial chemoreceptors (McQueen and Ribeiro, 1981) and studies using selective agonists suggested that this effect was mediated by A 2A receptors Ribeiro, 1983, 1986). In animals as well as humans, adenosine and its analogs cause sinus tachycardia and lower systemic blood pressure (Biaggioni et al, 1987;Lappe et al, 1992;Bonizzoni et al, 1995;Alberti et al, 1997;Koos and Chau, 1998;Barrett et al, 2005;Hendel et al, 2005;Schindler et al, 2005). The sinus tachycardia has been attributed to the baroreceptor reflex caused by the decrease in arterial pressure (Webb et al, 1990(Webb et al, , 1991Nekooeian and Tabrizchi, 1996;Alberti et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In animals as well as humans, adenosine and its analogs cause sinus tachycardia and lower systemic blood pressure (Biaggioni et al, 1987;Lappe et al, 1992;Bonizzoni et al, 1995;Alberti et al, 1997;Koos and Chau, 1998;Barrett et al, 2005;Hendel et al, 2005;Schindler et al, 2005). The sinus tachycardia has been attributed to the baroreceptor reflex caused by the decrease in arterial pressure (Webb et al, 1990(Webb et al, , 1991Nekooeian and Tabrizchi, 1996;Alberti et al, 1997). However, there is also evidence that adenosine-mediated tachycardia can occur independent of a decrease in MAP (Lappe et al, 1992;Mathot et al, 1995;Koos and Chau, 1998;Schindler et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increase in HR has been traditionally attributed to a reflex response to the vasodilatory effect on the systemic circulation and the resultant increase in sympathetic discharge. 5,6 The true mechanism of HR increase, however, is more complicated and involves direct stimulation of the sympathetic nervous system. 7 The administration of adenosine as a bolus, as done for the interruption of supra-ventricular tachycardias, has a negative chronotropic effect on the atrio-ventricular node via stimulation of the A1 receptor.…”
mentioning
confidence: 99%